Carotid aneurysm with intrasellar extension: a rare cause of panhypopituitarism - Alvarado, Hernán (2024)
Panhypopituitarism can be caused by various conditions; among them, a very rare cause is carotid aneurysms with intrasellar extension, though these account for less than 0,2 % . The described symptoms are divided into those caused by pituitary insufficiency and those caused by mass effect. We present the case of a 56-year-old female patient with a history of hypertension, hypothyroidism and a previous SARSCoV-2 infection. She was admitted to the hospital due to clinical features including fainting, decreased appetite, profuse sweating and persistent vomiting. During the evaluation she presented with stable vital signs, and a physical examination indicated pallor, with no significant alteration in the neurological examination. Furthermore, laboratory tests revealed hyponatremia, hypoglycemia and bicytopenia. The diagnosis was panhypopituitarism along with a large carotid aneurysm with intrasellar extension, detected by computed tomography angiography (CTA) and contrast-enhanced MRI. This case highlights the importance of considering a large or giant aneurysm with sellar compression as a rare differential diagnosis of panhypopituitarism, thereby contributing to medical knowledge and emphasizing the need to improve the anamnesis and clinical imaging studies. Furthermore, it is necessary to consider the different clinical features with which it can manifest, as well as the gradual occurrence of alterations in the hormonal axes and to recognize that not every brain lesion is indicative of a tumor. In the investigation of similar cases, it was found that most occur in patients older than 50 years, with different disease durations and with symptoms of mass effect at onset.